2015
DOI: 10.1117/2.1201412.005649
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating deformation at high temperatures

Abstract: Two novel deformation carrier fabrication methods, using nanoimprint lithography and micromachine technology, respectively, enable the measurement of mechanical behavior under thermal shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This article is protected by copyright. All rights reserved spraying particles, e.g., Ti (tested at 650-800 ℃) 13 , Au (tested at ~700 ℃) 14 , amorphous silica and TiO 2 8 , and CoO (tested at 1100 ℃) 15,16 , however, usability of these materials is limited below 1200 ℃ 17 . Tungsten coatings deposited by atmospheric plasma spraying (APS)were also used to improve the thermal stability of speckle patterns 18,19 .…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…This article is protected by copyright. All rights reserved spraying particles, e.g., Ti (tested at 650-800 ℃) 13 , Au (tested at ~700 ℃) 14 , amorphous silica and TiO 2 8 , and CoO (tested at 1100 ℃) 15,16 , however, usability of these materials is limited below 1200 ℃ 17 . Tungsten coatings deposited by atmospheric plasma spraying (APS)were also used to improve the thermal stability of speckle patterns 18,19 .…”
Section: Accepted Articlementioning
confidence: 99%
“…Recent studies also showed that DIC is an effective tool to understand heterogeneous deformation of fiber‐reinforced CMCs and ceramic coatings at high temperature in various scales 9 ; however, application of DIC at high temperature is limited by heat resistance of the speckle pattern. Various materials were investigated as spraying particles, for example, Ti (tested at 650‐800°C), 13 Au (tested at ~700°C), 14 amorphous silica and TiO 2 , 8 and CoO (tested at 1100°C) 15,16 ; however, usability of these materials is limited below 1200°C 17 . Tungsten coatings deposited by atmospheric plasma spraying (APS) were also used to improve the thermal stability of speckle patterns 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is suitable for measuring physical properties of a deformable object due to its ability to detect the displacements of points. The moiré interferometry has been employed in many types of materials such as solids, films and composites in measurement of mechanical properties, such as stress and strain, as well as in the study of crack propagation and morphogenesis [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This change will have a significant impact on the optical system, and even make it a failure for a lofty precision optical machine, which required little change of performance with the temperature. PbTe film is widely used in infrared optical film, especially in the far infrared region due to its interesting properties, such as a high refractive index and wide transparent region [8][9][10][11] . Currently, the refractive index of PbTe film under cryogenic conditions is commonly obtained by the fitting method and extrapolation [12][13][14] .…”
mentioning
confidence: 99%